STAGE AS KNOWLEDGE OF IMPELLER IN TEACHER TRAINING DISTANCE: NOTES AND REFLECTIONS (Fiep Bulletin - online, 2017)
We present in this work, teacher training, in the distance, while locus of reflection and construction of teacheridentity, taking the stage as preparation space / reconstruction of knowledge. Teacher training can be understood as a processthat enables learning to be a teacher at levels and specific contexts, in the professional field. The stage becomes a space in whichthe teaching knowledge classified into professional, disciplinary, curricular and experiential are mobilized and reworked. Thestage in both modes, face and distance, are governed by the same laws and the same academic functions. The study hasbibliographic character, with qualitative and deductive method. From this, it appears that the supervised in the distance may notbe something minimized, only to comply with a formality, but something planned, accompanied appropriately by teachers andtutors, to be something meaningful for those who experience the institutional space as teachers, in many cases as a firstexperience.